A 3D calcium-deficient hydroxyapatite-based scaffold with gold nanoparticles effective against Micrococcus luteus as an artificial bone substitute. (July 2022) - Kim, Hye-In; Raja, Naren; Kim, Jueun; Sung, Aram; Choi, Yeong-Jin; Yun, Hui-suk; Park, Honghyun
Graphical abstract: Highlight: D-printed CDHA scaffold was used as an artificial bone substitute and their interfaces were engineered by aminosilane to induce in-situ growth of Au NPs on the surface. In terms of ROS scavenging properties, a synergetic effect of Au NPs and CDHA facilitated sixty times enhanced antibacterial activities than the one of the commercial antibiotics. Au-scaffold is harmless toward cellular viability for real application as an artificial bone substitute. Abstract: During implant surgery, microbial contamination of implants is a major issue that must be addressed to avoid acute and chronic post-surgery infection that may result in acute inflammation, a lengthy healing period, and surgical failure. Bacteria and other microbes use reactive oxygen species (ROS) to send signals between microbes for their proliferation and propagation. Therefore, we developed a functional bone substitute comprised of a ceramic scaffold (Calcium-deficient hydroxyapatite, CDHA) and immobilized gold nanoparticles (Au-scaffold) to scavenge microbial ROS and suppress microbial proliferation at early stages. The Au-scaffold can selectively scavenge H2 O2 and ∙O2 -, and consequently, effectively inhibit the growth of Micrococcus luteus ( M. luteus ). In terms of antimicrobial activity, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the Au-scaffold against M. luteus are comparable to commercial antibiotics (e.g., ceftriaxone, ampicillin, streptomycin, gentamycin, and tetracycline). The Au-scaffold also shows higher cell viability than the commercial antibiotics. Thus, with its antimicrobial activity and low toxicity, the developed Au-scaffold has promising potential antibacterial activity against one of the major post-surgical infection bacteria, Micrococcus luteus.